Population Moderation as the Affect of Regional Taxes, Levies and GRDP on Regional Genuine Income - Angraini, Dila; Utami, Tri; Annisa, Dea (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2024)
Regional capability in implementing and realizing regional autonomy can be seen and measured from the realization of Regional Genuine Income, this is because RGI is part of the largest financial source for the implementation of regional autonomy. Regional Taxes and Regional Levies are important components in contributing to an increase in RGI. This research takes several variables that are thought to affect RGI including regional taxes, Regional Levies, Gross Regional Domestic Income (GRDP) and the moderating variable, namely population. This research was conducted to find out whether the independent variables, namely the independent factors that have been described previously, can affect the dependent variable, namely Regional Genuine Income. This research was tested using the Eviews application. The test results show that regional taxes have an effect on  Regional genuine income, Regional Levies and GRDP have no effect on regional genuine income, the population moderates regional taxes, and the population does not moderate Regional Levies and GRD